2020
DOI: 10.1039/d0tb00889c
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic bowl-like SERS substrates patterned from CMOS sensors for extracellular vesicle characterization

Abstract: Using a regular CMOS sensor as a template, we are able to fabricate a simple but highly effective superhydrophobic SERS substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Recent reports have demonstrated the ability of Raman spectroscopy to accurately distinguish PD 58 and Amyotrophic Lateral Sclerosis (ALS) 59 patients from healthy control group based on their EVs profile. Our group previously demonstrated the application of laser tweezers Raman spectroscopy for exosomes heterogeneity analysis 39 and surface-enhanced Raman spectroscopy for biochemical analysis of EVs [60][61][62][63][64] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have demonstrated the ability of Raman spectroscopy to accurately distinguish PD 58 and Amyotrophic Lateral Sclerosis (ALS) 59 patients from healthy control group based on their EVs profile. Our group previously demonstrated the application of laser tweezers Raman spectroscopy for exosomes heterogeneity analysis 39 and surface-enhanced Raman spectroscopy for biochemical analysis of EVs [60][61][62][63][64] .…”
Section: Introductionmentioning
confidence: 99%
“…PDMS was used to fabricate the superhydrophobic substrate with nanobowl and microbowl structures by the soft lithography method. Then, silver nanoparticles were grown in situ to impart SERS-enhancing properties ( Suarasan et al, 2020 ). Yang et al synthesized Fe 3 O 4 /Au/Ag nanocomposites and proposed a magnetically assisted SERS method to detect adenosine traces in clinical urine samples from lung cancer patients ( Yang et al, 2014 ).…”
Section: Different Types Of Superwettable Biosensorsmentioning
confidence: 99%
“…This method demonstrated a high diagnostic accuracy (98.6%), which is promising for rapid, high-throughput, and label-free screening for cancer ( Lin et al, 2021 ). With various designs of the superhydrophobic substrate, SERS-based superwettable biosensors have also been used to detect diverse cancer biomarkers, such as miRNA ( Song et al, 2018 ; Song X. et al, 2020 ), extracellular vesicles ( Suarasan et al, 2020 ), and peptides ( Perozziello et al, 2014 ). These methods provide enormous potential to construct POCT devices for the early diagnosis of cancer.…”
Section: Different Types Of Superwettable Biosensorsmentioning
confidence: 99%
“…For these reasons, they have been largely preferred for biosensing applications over direct approaches. Nonetheless, the current literature survey on exosome SERS analysis shows a larger number of reports based on direct approaches [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] than indirect ones [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. This apparent anomaly may be explained by taking into considerations the intrinsic exosomal heterogeneity that currently burdens the identification of specific disease-related biomarkers for selective separation and labelling of clinically relevant exosome subpopulations [ 90 , 99 , 102 ].…”
Section: Isolation and Characterization Of Exosomesmentioning
confidence: 99%
“…Small drops of exosome dispersions (~0.2 ng/mL) were deposited on the substrates ( Figure 7 C) and, through evaporation, the vesicles were conveyed into small plasmonic-active regions of the substrate ( Figure 7 D) for the acquisition of averaged SERS spectra (50 acquisitions for each sample). More recently, Suarasan et al [ 74 ] reported a simple, cheaper superhydrophobic plasmonic platform for SERS interrogation of exosomes in small sample volume (as low as 0.5 μL). A PDMS substrate consisting of nano- and micro-bowl structures exhibiting superhydrophobic properties was fabricated via soft lithography.…”
Section: Direct Label-free Sers Analysis Of Exosomesmentioning
confidence: 99%